PENGARUH JENIS PAKAN YANG BERBEDA TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN MANFISH (Pterophyllum scalare) - ratihpangesturahayu; Ayu Adhita Damayanti; Bagus Dwi Hari Setyono (Jurnal Perikanan Unram, 2019)
This study aims to determine the type of feed that supports growth and high survival for Manfish. The research was carried out for 30 days, which took place in the Self Installation. This research was conducted by an experimental method using a Completely Randomized Design (CRD) with 4 treatments and 3 replications. The treatment given is different feeding and each treatment is repeated 3 times. The treatments given are: Treatment 0 (control): feeding using tubifex, Treatment 1: feeding using mosquito larvae, Treatment 2: feeding using rebon shrimp, Treatment 3: feeding a combination of blood worms and rebon shrimp. The parameters observed were, absolute length, absolute weight, specific growth, survival rate and water quality. The results showed that there was no real effect of different types of feed on the growth and survival of manfish.